Cognitive styles and psychotic experiences in a community sample. - Sarah Sullivan; Richard P Bentall; Charles Fernyhough; Rebecca M Pearson; Stanley Zammit (PLoS ONE)
Introduction In clinical populations paranoid delusions are associated with making global, stable and external attributions for negative events. Paranoia is common in community samples but it is not known whether it is associated with a similar cognitive style. This study investigates the association between cognitive style and paranoia in a large community sample of young adults. Methods 2694 young adults (mean age 17.8, SD 4.6) from the ALSPAC cohort provided data on psychotic experiences and cognitive style. Psychotic experiences were assessed using a semi-structured interview and cognitive style was assessed using the Cognitive Styles Questionnaire-Short Form (CSQ-SF) on the same occasion. Logistic regression was used to investigate associations between paranoia and CSQ-SF scores, both total and domain-related (global, stable, self, external). The role of concurrent self-reported depressive symptoms in the association was explored. Results Paranoia was associated with Total CSQ-SF scores (adjusted OR 1.69 95% CI 1.29, 2.22), as well as global (OR 1.56 95% CI 1.17, 2.08), stable (OR 1.56 95% CI 1.17, 2.08) and self (OR 1.37 95% CI 1.05, 1.79) domains, only Total score and global domain associations remained after additional adjustment for self-reported depression. There was no association between paranoia and external cognitive style (OR 1.10 95% CI 0.83, 1.47). Conclusion Paranoid ideation in a community sample is associated with a global rather than an external cognitive style. An external cognitive style may be a characteristic of more severe paranoid beliefs. Further work is required to determine the role of depression in the association between cognitive style and paranoia.